Predominance of Duplicative VSG Gene Conversion in Antigenic Variation in African Trypanosomes - Robinson, Nicholas P. (American Society for Microbiology, 1999)
A number of mechanisms have been described by which African trypanosomes undergo the genetic switches that differentially activate their variant surface glycoprotein genes (VSGs) and bring about antigenic variation. These mechanisms have been observed mainly in trypanosome lines adapted, by rapid syringe passaging, to laboratory conditions. Such “monomorphic” lines, which routinely yield only the proliferative bloodstream form and do not develop through their life cycle, have VSG switch rates up to 4 or 5 orders of magnitude lower than those of nonadapted lines. We have proposed that nonadapted, or pleomorphic, trypanosomes normally have an active VSG switch mechanism, involving gene duplication, that is depressed, or from which a component is absent, in monomorphic lines. We have characterized 88 trypanosome clones from the first two relapse peaks of a single rabbit infection with pleomorphic trypanosomes and shown that they represent 11 different variable antigen types (VATs). The pattern of appearance in the first relapse peak was generally reproducible in three more rabbit infections. Nine of these VATs had activated VSGs by gene duplication, the tenth possibly also had done so, and only one had activated a VSG by the transcriptional switch mechanism that predominates in monomorphic lines. At least 10 of the donor genes have telomeric silent copies, and many reside on minichromosomes. It appears that trypanosome antigenic variation is dominated by one, relatively highly active, mechanism rather than by the plethora of pathways described before.